Socialization Of Early Marriage Prevention As A Means Of Reducing Divorce Rates - Intan Permata Putri; Umi Zahro; Novi Yuliati; Maulia Aryani Rofiqoh; Safeta Weyla Samti Ardhania; Faiza Izzata Aulia; Muhamad Agil Dalla Ramadani; Fadia Nur Amalia; Sandya Kliana Kurnia Dewi; Muhammad Khudori (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Several countries face the problem of early marriage. Child marriage occurs in both urban and rural areas, with various backgrounds and economic classes. Economics, education, demographics and socio-culture influence early marriage in developing countries. Early marriage can also lead to divorce because they are not physically and mentally ready, so there are often disputes and so on. Adolescents who marry before the appropriate biological or psychological age are particularly vulnerable to adverse impacts. The community-based participatory research (CBPR) method was used in this study to address the need for a more people-centered and community-driven research approach to combat growing health disparities. The results of this study show that a movement such as socialization of early marriage prevention is needed in order to reduce the number of early marriages in Indonesia. After the number of early marriages in Indonesia is reduced, it will certainly correlate with the divorce rate in Indonesia because one of the factors of divorce is early marriage.